'Seeing the bigger picture': a post-graduate online learning community facilitates political competence for occupational therapists. Issue 7 (8th August 2020) - Walsh, Susan; Pollard, Nick
ABSTRACT: Occupational therapists are increasingly required to work beyond traditional health-care settings in new and emerging community roles. This study explored the learning experiences of a cohort of international students studying an online post-graduate module aimed at facilitating political competence. The evaluation used an ethnographic approach and methods included online data from online communication tools: semi-structured interviews, and tutors' reflective diaries. Data were subjected to thematic analysis. Results showed shifts in students' knowledge, skills and attitudes in seeing the bigger picture; developing collaborative partnerships and navigating the politics of practice at the margins of personal, political and professional positions. Themes from learning which promoted changes were interacting with online resources, valuing and sharing experiences, a safe and supportive environment, integrated learning and assessment, critical self and peer review. Importantly the democratic approach of online learning was shown to align with the principles of political and critical occupational therapy practice. Online learning within an international community can extend opportunities for developing professional knowledge and behaviours in the politics of community-based practice.